BODY SHAMING DAN PERUBAHAN PERILAKU SOSIAL KORBAN (STUDI PADA REMAJA DI KOTA DENPASAR) - Surya Wijaya, A.A. Gede; Kebayantini, Ni Luh Nyoman; Krisna Aditya, I Gusti Ngurah Agung (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
ABSTRACT Lifestyle trends develop among adolescents lead to bullying for those who donâ€™t follow the trends related to body image in supporting their appearance. Finally, it will lead to body shaming behavior, especially for adolescents who donâ€™t follow or comply with the ideal standards that grow in the society. This study conducts to analyze the changes in the social behavior of victims due to the impact of body shaming that occurs in adolescents in Denpasar. This research uses a descriptive and explanative qualitative approach. The theory used in this research is the social attribution theory from Fritz Heider. The impact of body shaming on adolescents is a cause and effect which makes the victims experience changes in their social behavior. On the other side, body shaming has given rises to the term â€œbody positivityâ€, which is another term for action in the form of peopleâ€™s appreciation for their physical look. Keywords: Bullying, body shaming, body image, lifestyle.